Slow Relaxation of Magnetization in an Isostructural Series of Zinc–Lanthanide Complexes: An Integrated EPR and AC Susceptibility Study. Issue 36 (28th July 2016) - Amjad, Asma; Madalan, Augustin M.; Andruh, Marius; Caneschi, Andrea; Sorace, Lorenzo
Abstract: We report the synthesis, structure, and spectroscopic and dynamic magnetic properties of a series of heterodinuclear complexes, [ZnLn(LH4 )2 ](NO3 )3 ⋅ 6 H2 O (Ln=Nd, Tb, Dy, Ho, Er, and Yb), with the singly deprotonated form of a new compartmentalized Schiff‐base ligand, LH5 . The Ln III ions in these systems show a distorted square‐antiprism geometry with an LnO8 coordination sphere. EPR spectroscopy and DC magnetic studies have shown that the anisotropic nature of the complexes is far more complicated than predicted on the basis of a simple electrostatic model. Among the investigated systems, only the Dy III derivative showed single‐ion magnet behavior, in zero and an applied magnetic field, both in pure polycrystalline samples and in a series of polycrystalline samples with different degrees of dilution at the single‐crystal level in the isostructural Y III derivative. The rich dynamics observed as functions of frequency, field, and temperature reveals that multiple relaxation mechanisms are at play, resulting in a barrier of 189 cm −1, which is among the highest reported for a dinuclear Zn–Dy system. Analysis of the dynamic behavior as a function of dilution degree further evidenced the persistence of non‐negligible intermolecular interactions, even at the lowest concentration of 1 %. Abstract : An attractive pair : EPR spectroscopy and DC magnetic studies have been used to probe the anisotropic magnetic properties of a series of Zn–Ln compounds, revealing clear deviations from behavior predicted on the basis of a simple electrostatic model (see graphic). The Dy III derivative further showed rich magnetization dynamics, for which multiple relaxation mechanisms have been identified. Its activation barrier is one of the highest reported for a dinuclear Zn–Dy system.